PENGARUH KOMUNIKASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PT. SUVARNA LAND JAKARTA - Eneng Dea Ratnasari; Arief Rachmawan Assegaf (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This research aims to analyze the influence of communication and service quality on consumer satisfaction PT Suvarna Land Jakarta. The method used in this research is a quantitative method with a survey approach. Data was collected through a questionnaire distributed to respondents who were consumers of PT Suvarna Land Jakarta. The research results show that both communication and service quality have a significant and positive influence on customer satisfaction, and simultaneous communication and service quality have a significant influence on customer satisfaction of PT Suvarna Land Jakarta.